2012
DOI: 10.1016/j.ajog.2012.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lidocaine for IUD insertional pain: a randomized controlled trial

Abstract: Objective Anticipated pain with intrauterine device (IUD) insertion may be a barrier to widespread use. Our objective was to evaluate the efficacy of intracervical 2% lidocaine gel for pain relief with IUD insertion. Study Design We performed a double-blind, randomized controlled trial of women undergoing IUD insertion. Participants were randomly assigned to 2% lidocaine or placebo gel. Study gel (3ccs) wase placed 3 minutes prior to IUD insertion. Pain scores were measured at various time points using a 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 31 publications
1
29
1
1
Order By: Relevance
“…However, reducing pain with IUD insertion among nulliparous women may increase the acceptability of this highly effective contraceptive method for this group. NSAIDs, intracervical lidocaine [28], nitric oxide donors [21,22] and misoprostol [29] have all been studied, but none have been shown to be effective. Given the important public health need to reduce barriers to IUD utilization overall, further investigations should concentrate on alternate strategies to reduce pain and improve satisfaction with IUD insertion among nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…However, reducing pain with IUD insertion among nulliparous women may increase the acceptability of this highly effective contraceptive method for this group. NSAIDs, intracervical lidocaine [28], nitric oxide donors [21,22] and misoprostol [29] have all been studied, but none have been shown to be effective. Given the important public health need to reduce barriers to IUD utilization overall, further investigations should concentrate on alternate strategies to reduce pain and improve satisfaction with IUD insertion among nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials examined the use of 2% lidocaine gel placed intracervically prior to tenaculum placement and IUD insertion. 18,19,46 None of the studies found improvement in pain scores with tenaculum placement or IUD insertion. Nelson and Fong 47 conducted a randomized controlled pilot study of 40 women to examine the 92 Obstetrical and Gynecological Survey use of 1.2 mL of 2% lidocaine infused intrauterine prior to IUD insertion compared with saline.…”
Section: Intrauterine Device Insertionmentioning
confidence: 91%
“…The use of 2% lidocaine gel on the anterior lip of the cervix 3 minutes prior to tenaculum placement has been found to be no better than placebo gel in studies of IUD insertion. 18,19 On the other hand, 2 mL of injected 1% lidocaine decreased pain during tenaculum placement when compared with no injection in a trial evaluating paracervical block for IUD insertion. 20 Furthermore, a recent randomized controlled trial among 70 women compared a 2-mL injection of 1% lidocaine and 1 mL of 2% lidocaine gel to the anterior lip of the cervix for tenaculum placement.…”
Section: Tenaculum Placementmentioning
confidence: 98%
“…6,7,8 McNicholas et al randomized 199 women to either Lidocaine or placebo gel groups and applied gels to both ectocervix and endocervix (via catheter). 9 Tenaculum and IUD were applied 3 minutes after the gel is used, and pain scores were found to be statistically similar. Short waiting time in this study may be speculated to limit diffusion of the gel to the sensory nerves.…”
Section: Discussionmentioning
confidence: 91%